A new patent processing suite for academic and research purposes. (December 2016) - Reymond, David; Quoniam, Luc
Abstract: Patent databases are a counterpart of a technical encyclopedia providing a valuable informational source from patent documents. Patents apply to a wide variety of uses, and this is expanding. The increasing kinds of users of patent documents result in a lack of educational programs regarding this matter. This paper describes Patent2Net (P2N) a patentinformatic suite whose purpose is to fill the lack in the academic world (education and research) of a tool to use with students (STEM, Masters, PhD), by valuation services and for defining corpuses for research in general patent analysis, specifically on textual content. P2N is a free open-source modular, scalable, customizable and derivable tool, written in the python language. We present here the main functions of the tool and the technical aspects after discussing the skills to be reached by students for state of the art patent analysis.